Efektivitas Belanja Pendidikan dan Kesehatan terhadap Indeks Pembangunan Manusia: Analisis Regresi Nonparametrik - Misbahuddin; Andi Rahmat Nizar Hidayat; Tri Cahyo Nugroho; Irfan. B; Mahrani (PT. Palem Edukasi Nusantara, 2025)
This study analyzes the effectiveness of provincial government spending on education and health in relation to the Human Development Index (HDI) in Indonesia using a nonparametric regression approach. Cross-sectional data from 34 provinces for the year 2025, obtained from the Central Statistics Agency (BPS) and the Ministry of Finance, were utilized. The Nadaraya-Watson kernel regression method was applied to capture the nonlinear relationship between public spending and HDI without imposing a predetermined functional form, while conventional linear regression was used for comparison (R² = 0.43). The results reveal a nonlinear relationship with three distinct phases: rapid initial growth, stable growth, and a plateau indicating diminishing returns. Based on spending effectiveness, provinces were classified as high (6 provinces), medium (18 provinces), and low (10 provinces). Provinces with low performance exhibited high spending but lower-than-predicted HDI, indicating inefficiencies in governance and program implementation. These findings highlight that the success of human development is not solely determined by the size of the budget, but also by the quality of fiscal governance and implementation capacity. The study recommends evidence-based budgeting, strengthening fiscal governance, and targeted capacity-building support for low-performing provinces to enhance the effectiveness of public spending.